Agonie, perte ou renouveau d’une esthétique oubanguienne ? - Andrea Ceriana Mayneri (Images Re-Vues)
André Gide and Marc Allégret witnessed a ganza initiation dance of the Banda of Oubangui-Chari in Bambari in 1925. While Allégret filmed the spectacle, Gide jotted down a few pages expressing disappointment at the performance organized for Whites passing through. But the French writer and, for different and sometimes conflicting reasons, the administrators and missionaries to whom we owe our earliest ethnographic information on the Banda, were both dreaming of the authenticity of a non-existent ceremony that, for them, was necessarily part of a remote past. By contrast, the images from the first half of the century – photographs, filmed scenes, drawings executed by Europeans who passed quickly through these regions – show that very early on some Banda groups had begun to modify the ganza dance so as to introduce extraneous features and begin a process (which is still evolving) of resemanticizing the initiatory artefacts. This article presents some of these colonial images: an analysis of them reveals, above all, the gaze that, time and again, has weighed on Central African societies, but also allows us to advance some hypothesis on the more recent destiny of these artefacts, which, in the absence of the original initiatory contexts, continue to be reconstructed, sometimes modified, and to be given new significance. Their display arouses ambivalent reactions in the populations, where appreciation of and nostalgia for the past combine with panic at the danger represented by objects of witchcraft.